A source of resistance against yellow mosaic disease in soybeans correlates with a novel mutation in a resistance gene - Rahman, Saleem Ur; Raza, Ghulam; Naqvi, Rubab Zahra; McCoy, Evan; Hammad, Muhammed; LaFayette, Peter; Parrott, Wayne Allen; Amin, Imran; Mukhtar, Zahid; Gaafar, Abdel-Rhman Z.; Hodhod, Mohamed S.; Mansoor, Shahid (Frontiers in Plant Science, 2023)
Yellow mosaic disease (YMD) is one of the major devastating constraints to soybean production in Pakistan. In the present study, we report the identification of resistant soybean germplasm and a novel mutation linked with disease susceptibility. Diverse soybean germplasm were screened to identify YMD-resistant lines under natural field conditions during 2016-2020. The severity of YMD was recorded based on symptoms and was grouped according to the disease rating scale, which ranges from 0 to 5, and named as highly resistant (HR), moderately resistant (MR), resistant (R), susceptible (S), moderately susceptible (MS), and highly susceptible (HS), respectively. A HR plant named “NBG-SG Soybean” was identified, which showed stable resistance for 5 years (2016-2020) at the experimental field of the National Institute for Biotechnology and Genetic Engineering (NIBGE), Faisalabad, Pakistan, a location that is a hot spot area for virus infection. HS soybean germplasm were also identified as NBG-47 (PI628963), NBG-117 (PI548655), SPS-C1 (PI553045), SPS-C9 (PI639187), and cv. NARC-2021. The YMD adversely affected the yield and a significant difference was found in the potential yield of NBG-SG-soybean (3.46 ± 0.13a t/ha) with HS soybean germplasm NARC-2021 (0.44 ± 0.01c t/ha) and NBG-117 (1.12 ± 0.01d t/ha), respectively. The YMD incidence was also measured each year (2016-2020) and data showed a significant difference in the percent disease incidence in the year 2016 and 2018 and a decrease after 2019 when resistant lines were planted. The resistance in NBG-SG soybean was further confirmed by testing for an already known mutation (SNP at 149th position) for YMD in the Glyma.18G025100 gene of soybean. The susceptible soybean germplasm in the field was found positive for the said mutation. Moreover, an ortholog of the CYR-1 viral resistance gene from black gram was identified in soybean as Glyma.13G194500, which has a novel deletion (28bp/90bp) in the 5`UTR of susceptible germplasm. The characterized soybean lines from this study will assist in starting soybean breeding programs for YMD resistance. This is the first study regarding screening and molecular analysis of soybean germplasm for YMD resistance.